NEW MECHANISM ON PROTECTING CIVIL RIGHTS OF VULNERABLE GROUPS IN VIETNAM - OPPORTUNITIES AND CHALLENGES - The, Nguyen Thi (Veredas do Direito, 2026)
The National Assembly’s authorization for the People's Procuracy to pilot the filing of civil lawsuits to protect the civil rights of vulnerable groups (disadvantaged subjects) is a historic step forward, demonstrating the determination of the Vietnamese State in realizing the goal of protecting human rights and citizens' rights. With the new mechanism on protecting the civil rights of vulnerable subjects, the role of the People's Procuracy as the "gatekeeper of justice" is clearly demonstrated; at the same time, it has breakthrough significance in protecting vulnerable groups by realizing their right to access justice, promoting social equity, and contributing to sustainable national development. However, along with new opportunities, protecting the civil rights of vulnerable groups through the mechanism of the People's Procuracy initiating civil lawsuits also poses challenges, requiring timely and synchronous solutions to enhance the effectiveness of the pilot implementation in the coming time.